(untitled) (Constructionism Conference Proceedings, 2025)
Young learners today find themselves in an increasingly complex and digitalized world. Accordingly, educational research, policy and practice need to develop and implement modern frameworks and approaches that foster critical and self-determined engagement with corresponding challenges. Computational Empowerment (CE) represents a recent development in response to this need. It applies ideas inherent to participatory design and constructionist learning in order to promote digital literacy and a creative, hands-on approach to engaging with digital technology. Despite its proven potential, CE has yet received little room in formal education. This paper focuses on two key problems in this regard: difficulties with assessment and the limited role of CE in teacher education, both of which hinder its adoption in schools. To explore these issues, the paper analyzes 17 student reflections on assessing CE-based projects. It examines students’ assessment strategies, including criteria, methods and challenges. Based on the findings, the paper highlights key challenges and, consequently, proposes strategies for advancing CE in formal education.